Hot Music, Ragmentation, and the Bluing of American Literature - Tracy, Steven C. (Steven Carl), 1954- (Book collections on Project MUSE., 2015)
Exploring the deep and enduring relationship between music and literature, Hot Music, Ragmentation, and the Bluing of American Literature examines the diverse ways in which African American "hot" music influenced American culture-particularly literature-in early twentieth century America. Steven C. Tracy provides a history of the fusion of African and European elements that formed African American "hot" music, and considers how terms like ragtime, jazz, and blues developed their own particular meanings for American music and society. He draws from the fields of literature, literary